2004
DOI: 10.1080/09603120400004048
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis in Imo state, Nigeria (2): the prevalence, intensity and distribution in the upper Imo river basin

Abstract: Human infection with Onchocerca volvulus was investigated in 13 rural communities in the Upper Imo River basin, Imo State, Nigeria between March 1997 and December 2000 using the skin snip method. Of the 3,311 persons examined, 889 (26.8%) had microfilariae. There were significant differences between communities in microfilariae prevalence and intensity of infection (P<0.05). Sex infection was similar in males (26.8%) and females (26.9%); whereas farmers (46.6%) and fishermen (28.4%) were more affected than peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
(23 reference statements)
2
11
0
Order By: Relevance
“…This suggests that individuals that are engaged in activities such as farming and hunting especially around the river are likely to be exposed to the blackfly bites and consequently have higher infection rate and worm loads (intensity) as observed in Idogun community. This was in agreement with the finding of Ikechukwu et al [15] , who reported prevalence of 46.6% among the farmers in Imo State. The total prevalence of infection in Idogun (28.1%) community suggests that the community is hypo-endemic (16-39%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that individuals that are engaged in activities such as farming and hunting especially around the river are likely to be exposed to the blackfly bites and consequently have higher infection rate and worm loads (intensity) as observed in Idogun community. This was in agreement with the finding of Ikechukwu et al [15] , who reported prevalence of 46.6% among the farmers in Imo State. The total prevalence of infection in Idogun (28.1%) community suggests that the community is hypo-endemic (16-39%).…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in accordance with the findings of other groups [10,[12][13][14]. But contrary to the report of Ikechukwu et al [15] who reported that the sex prevalence in upper river basin in Imo State was not different between the gender. Similarly, farming, fishing and hunting were identified as major socio-economic activities that highly predisposed the respondents to the infection.…”
Section: Discussionsupporting
confidence: 92%
“…In the Central African Republic, a study conducted in 1996 reported a positive and significant correlation (r = 0.73; P < 0.001) between onchocerciasis endemicity levels determined by community microfilarial levels (hypoendemic, mesoendemic, and hyperendemic) and epilepsy prevalence (respectively, 0.5%, 0.8%, and 2.5%), and a negative and significant correlation (r = -0.34; P < 0.03) between epilepsy prevalence and mean distance from the nearest river of the villages in each endemicity level (respectively, 9.5, 5.9, and 2.4 Km) [57]. A positive correlation between epilepsy and onchocerciasis, albeit being weaker, was also observed in the Imo river basin in Nigeria: (r = 0.38; P < 0.043) [39,58].…”
Section: Consistencymentioning
confidence: 99%
“…volvulus infection has been reported in all age groups, from children younger than 10 years to adults over 50 years of age. Although not always consistent, reports have generally revealed an increase in the prevalence of onchocerciasis with increasing age (see Table 1) [12][13][14][15][95][96][97][98][99][100], and the duration of stay in an onchocerciasis-endemic community is thought to be one of the main predictors of onchocercal infection [13]. This may be ascribed to the fact that the rate of larval stage 3 infecting the human host is greater than the rate of death of the adult worms [13,15,95,96,98,101].…”
Section: Clinical Spectrum Of Onchocerciasis and Ageingmentioning
confidence: 99%
“…Several studies have unequivocally revealed an increase in the prevalence of onchocerciasis infection among older people, aged 50 years and above, living in endemic regions [12][13][14][15]. Most lymphatic complications, skin and eye lesions due to onchocerciasis are more frequent among the elderly population.…”
Section: Introductionmentioning
confidence: 99%